2013
DOI: 10.1097/iio.0b013e31829ced74
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Rupture

Abstract: First described in 1854 by von Graefe, 1 a choroidal rupture is a break in the choroid, the Bruch membrane, and retinal pigment epithelium (RPE). Here, we review the causes, pathophysiological basis, clinical and imaging findings, complications, prognosis, and treatments for choroidal ruptures. ' CausesChoroidal ruptures have been reported in up to 5% to 10% of cases of blunt ocular trauma but can also occur in the setting of penetrating or perforating injuries. [2][3][4] In one study of 111 cases of choroidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
0
9
0
2
Order By: Relevance
“…CR has been reported in 5%–10% of cases of blunt ocular trauma. [ 5 ] It may occur directly at the site of impact or more commonly at a site distant from the place of injury due to countercoup mechanism. [ 5 ] Various hypotheses have been postulated to explain the genesis of CR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CR has been reported in 5%–10% of cases of blunt ocular trauma. [ 5 ] It may occur directly at the site of impact or more commonly at a site distant from the place of injury due to countercoup mechanism. [ 5 ] Various hypotheses have been postulated to explain the genesis of CR.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] It may occur directly at the site of impact or more commonly at a site distant from the place of injury due to countercoup mechanism. [ 5 ] Various hypotheses have been postulated to explain the genesis of CR. Sudden anteroposterior deformation of the globe following trauma with subsequent equatorial expansion has been incriminated for CR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that choroidal injuries were observed in 69.7% of all the eyes with no light perception and were estimated as a predictor of poor prognosis (3). Traumatic choroidal injuries are not uncommon in clinical practice, and a variety of choroidal injuries have been reported (4)(5)(6)(7). In our recent study (8), we summarized traumatic choroidal injuries into nine categories, including suprachoroidal effusion, suprachoroidal hemorrhage, massive suprachoroidal hemorrhage, choroidal avulsion, traumatic chorioretinal rupture, choroidal rupture, choroidal loss, choroidal hole, and choroidal damage at the wound site, and a classification system for traumatic choroidal injuries was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Classically, we distinguish two types of globe injuries: open and closed (indirect tissue damage), which could be complicated by a CR in 30% and 70%, respectively. 2 The visual prognosis of CR depends on its localization and on macular complications. Choroidal neovascularization is associated with 20% of indirect CR.…”
mentioning
confidence: 99%